Efektivitas Seminar Edukatif dalam Meningkatkan Kesadaran dan Perilaku Anti-Bullying Siswa SMP Negeri 56 Bandung - Cucu Robiatul Adawiah; Edward Rifaldy Solehudin; Nila Syafitrti Hasibuan; Rihan Rizky (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effectiveness of an educational seminar in increasing anti-bullying awareness and behavior among students at SMP Negeri 56 Bandung. The research was conducted using a descriptive qualitative approach supported by quantitative data obtained from questionnaires administered before and after the seminar. The seminar was designed through interactive lectures, audio-visual media, group discussions, and reflective activities to strengthen students’ understanding and engagement. The findings indicate a significant improvement in students’ cognitive awareness regarding the forms and impacts of bullying, including physical, verbal, social, and cyberbullying. In addition, students demonstrated positive affective changes marked by increased empathy, social sensitivity, and emotional rejection of bullying behaviors. Behavioral outcomes were also evident, as students showed greater willingness to take preventive actions such as speaking up, supporting victims, reporting incidents, and promoting a respectful school climate. The seminar fostered student participation as active contributors in creating a safe and inclusive learning environment.